Rekognisi Status dan Perlindungan Hukum Pekerja Gig Economy: Tinjauan Tuntutan Kolektif Pengemudi Ojek Online di Indonesia - Alfin Dwi Novemyanto; Rismawati Nur (JURNAL HUKUM PELITA, 2025)
Digital transformation has created new forms of employment within the framework of the gig economy, one of which is online motorcycle taxi drivers (ojol). Despite their importance, these drivers lack defined legal status. As a result, they don’t receive labor protection equivalent to that of formal workers. This legal uncertainty has triggered various collective demands, including the provision of religious holiday allowances (THR), regulation of minimum fares, commission limits, and access to social security. This study aims to analyze the urgency of legal recognition for gig economy workers, identify forms of maladministration in the governance of digital labor, and propose regulatory reforms to strengthen legal protection for ojol drivers. The research used normative legal research with statutory and conceptual approaches. The results showed that partnership status unilaterally constructed by platforms creates a pseudo-partnership that contradicts the principles of worker protection. The state is considered negligent in regulating fare systems, supervising commissions, and providing adaptive legal protection. Therefore, regulation through specific legislation (lex specialis), judicial review of exclusive norms, and the application of soft law in the digital transport sector are necessary. Recognizing gig economy workers as legal subjects is essential for creating an inclusive, fair, constitutional labor system